Synthesis, Structure, Antibacterial Activity, and Hirshfeld Surface Analysis of Complex [Co(4-ampy)4(NCS)2]·CO2 - Savitri, Linggar Agil; Putra, Faaza'izzahaq Setta; Laksmana, Sutandyo Dwija; Mariyam, Dewi; Dasna, I Wayan (Universitas Gadjah Mada, 2024)
The [Co(4-ampy)4(NCS)]2·CO2 complex compound was successfully synthesized using the reflux method from the reaction between CoCl2·6H2O, 4-aminopyridine, and KSCN in methanol solvent for 6 h at 64 °C. The synthesized compound is a dark purple cube-shaped crystal with a melting point of 209 °C. FTIR test showed the presence of isothiocyanate anion at C=N stretching vibration wavenumber 1633 cm−1, C–N vibration on amine group belonging to 4-aminopyridine ligand at 1217 cm−1, and C=N vibration of pyridine aromatic group at 1334 cm−1. Single crystal X-ray diffraction data refinement results show the complex compound has octahedral geometry in a cubic lattice with space group Pn̄3n with lattice parameters a = b = c = 16.426(3) Å and α = β = γ = 90°. According to the crystal data, there was one molecule of CO2 in the crystal packing of the complex. Hirshfeld surface analysis showed the major interaction contributions from C⋯H/H⋯C, H⋯H, S⋯H/H⋯S, and O⋯H/H⋯O. The antibacterial activity test results showed that the activity of the synthesized complex was more active against Staphylococcus aureus but less effective against Escherichia coli.